URGENCE AND CHALLENGES OF REGULATION OF AMICUS CURIAE IN THE JUDICIAL SYSTEM - Suntoro, Agus (Jurnal Hukum dan Peradilan, 2022)
The judicial system in Indonesia is dynamic and adaptive to the development of science and law, not least within the scope of the Supreme Court of the Republic of Indonesia, one of which relates to the amicus curiae (friends of the judiciary). In practice, amicus curiae are generally presented in cases or trials that get public attention and the livelihoods of many people, such as the environment, land, labor, and so on. Nevertheless, there is no regulation or Supreme Court Regulation on the application of amicus curiae in the trial, but various practices have occurred within the court. This paper will discuss: (a) how the concept of amicus curiae is in the justice system in several countries, (b) the practice and application of amicus curiae in the judiciary in Indonesia, and (c) the opportunity for the Supreme Court to issue regulations or circulars that seek to regulate the implementation of the amicus curiae as part of legal developments in Indonesia. This writing uses a qualitative method with a normative juridical approach. The results of this paper conclude that amicus curiae have become a good practice in the judicial system in Indonesia, especially in public cases, and the Supreme Court has the authority to make arrangements through PERMA as a foundation and procedure guide for all judicial personnel and society in Indonesia.